A CONTEMPORARY ISLAMIC LEGAL REVIEW OF MUḌĀRABAH CONTRACTS BASED ON THE DSN-MUI FATWA - Hamdan Fathurrahman; Nofrianto; Yuke Rahmawati; Fadli Daud Abdullah; Syahid Mujahid Wiwaha (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose: This study aims to review the muḍārabah contract from a contemporary Islamic legal perspective, particularly through the fatwas of the National Sharia Council (DSN-MUI), given its strategic role in Islamic financing practices in Indonesia. This study aims to analyze the development of the muḍārabah concept from a classical fiqh understanding to a more contextual and systematic regulation, as outlined in the DSN-MUI fatwas. Method - This study uses a qualitative research method with a normative-juridical approach, analyzing classical fiqh texts, contemporary literature, and DSN-MUI fatwas related to muḍārabah. Findings - The research findings show that although the basic concept of muḍārabah in Islamic jurisprudence emphasizes the principle of profit-sharing and full responsibility for losses on the part of the owner of the capital, the National Sharia Council (DSN-MUI) has developed it through more systematic regulations, such as recognizing legal entities as parties to the contract, guarantee mechanisms under certain conditions, and adapting muḍārabah to modern financial instruments such as sukuk, convertible bonds, and Islamic insurance. Research Contribution–This study provides a comprehensive understanding of the transformation of the muḍārabah contract from a classical concept to the context of Indonesian Islamic economic law. The limitation of this research lies in its limited focus on DSN-MUI fatwas without exploring their practical implementation in Islamic financial institutions. Originality: This study’s originality lies in its attempt to critically connect classical fiqh studies with contemporary fatwas, thereby enriching Islamic legal discourse in responding to modern challenges.